The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4300/jgme-03-03-30
|View full text |Cite
|
Sign up to set email alerts
|

Internal Medicine Residents' Acceptance of Self-Directed Learning Plans at the Point of Care

Abstract: Objectives We implemented a curriculum using self-directed learning plans (SDLPs) based on clinical questions arising from the residents' practice, and we report on perceptions and attitudes from residents in internal medicine regarding the use of SDLPs conceived at point of care. Methods Internal medicine residents at a single community hospital in the Midwest were surveyed in 2006 regarding SDLPs. We report their perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…SDL is felt to be integral to resident learning and identity formation [ 1 ]. Residency programs have implemented individualized learning plans to augment SDL [ 22 24 ]. Despite these efforts, residents have identified difficulty with SDL and desired guidance from faculty [ 19 , 20 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…SDL is felt to be integral to resident learning and identity formation [ 1 ]. Residency programs have implemented individualized learning plans to augment SDL [ 22 24 ]. Despite these efforts, residents have identified difficulty with SDL and desired guidance from faculty [ 19 , 20 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…90 Multiple studies on residents' active learning in clinical contexts have highlighted the importance of scaffolding their learning opportunities to foster their feelings of competence and autonomy, similar to medical students. 91,92 Other studies have shown additional similarities, such as how residents' active learning in clinical contexts also varies to include both planned and reactive learning, 93 how questions of others (such as the patient) may be strong motivators for goal setting in active learning, 94 and how individualised learning plans may be helpful to support active learning. 94 To guide this learning, vocational training curricula have often been using competency frameworks to plan lifelong learning activities.…”
Section: Vocational Training Phasementioning
confidence: 99%
“…91,92 Other studies have shown additional similarities, such as how residents' active learning in clinical contexts also varies to include both planned and reactive learning, 93 how questions of others (such as the patient) may be strong motivators for goal setting in active learning, 94 and how individualised learning plans may be helpful to support active learning. 94 To guide this learning, vocational training curricula have often been using competency frameworks to plan lifelong learning activities. 95 However, learners in vocational training are known to struggle with this.…”
Section: Vocational Training Phasementioning
confidence: 99%
“…A review of the literature regarding PBLI suggests that self-directed learning (SDL) is one of the main components of PBLI, which requires a range of skills. Today, the professional world demands documentation of SDL to renew professional licenses (10,11). To identify the strengths and weaknesses, the self-reflection process should be integrated in daily medical responsibilities.…”
Section: Components Of Pblimentioning
confidence: 99%